An enhancement in parallel cascade scheme for non-minimum phase system. (6th March 2023) - Yadav, Manish; Patel, Hirenkumar G.
This paper aims to control non-minimum phase (NMP) systems with dead time in the existence of uncertainty and disturbances. The parallel cascade control is utilised to motivate such problems, especially for slow process dynamics and actuator nonlinearities. The work's novelty is combining a higher-order fractional-filter with an inverse response and dead-time compensator in the internal model control (IMC) framework for designing the outer loop controller. The conventional IMC scheme is adopted for the design of inner loop controller. This modified structure is offered refinement in the gain margin for better robustness. The Riemann sheet principal investigates fractional quasi characteristic polynomial arising from the non-minimum phase systems with dead time. Further, a robustness test is also carried out via sensitivity analysis. The efficacy of the suggested method is illustrated via two case studies.